Natural Compounds as Antimicrobial Agents - Carlos Manuel Franco; Beatriz I. Vázquez (MDPI AG, 2020)
During the first two decades of this century, conventional antimicrobial compounds have been found out to have more bacterial resistance. What has also been worrying is the rediscovery of the so-called "natural compounds", which in turn have a good name among the average citizen because of the former's plant or animal origin. However, they do not form a well-classified group of substances. This Special Issue consists of five reviews focusing on clinical bacteria applications in food and their specific effects upon virulent bacterial factors. You will also find a research on much needed, new antimicrobials sourced in extreme environments, and secondary metabolites of Burkholderia. This issue includes 12 original research papers which will provide you with an in-depth coverage of the protein extract activity, as well as the activity of other plant extracts, on fighting bacteria, fungi or diarrhea. Their use in broilers or laying eggs for production purposes has also been focused on in order to improve gut microbiota. Last but not least, we should not forget about honey and its effect; Allium sativum-fermented extracts, as well as other "natural" compounds, have been studied in their fight against biofilms. Furthermore, we have also examined the use of essential oils, which are currently used in edibles such as fresh sausages. The present work also deals with other applications such as natural compound derivatives as well as compound mixtures.